Anxiety and coping in women with breast cancer in chemotherapy - Araceli Vicente da Silva; Eliana Zandonade; Maria Helena Costa Amorim
ABSTRACT Objective: to identify the coping strategies used by women with breast cancer in chemotherapy and to verify the association with the anxiety profile presented by them. Method: cross-sectional study of the analytical type. We used a random sample of 307 women with cancer in previous chemotherapy, adjuvant or palliative treatment. The data was collected using an interview technique with form registration, active search in medical records, Scale of Mode of Confronting Problems and Inventory of Anxiety and State. The Statistical Package for Social Sciences 19.0, Pearson correlation coefficient and the test Mann-Whitney were used. Results: there was a significant association of the anxiety trait and problem-focused coping strategies with a focus on emotion (p<0,000) and the anxiety state with problem-focused coping (p=0,001) and with focus on emotion (p=0,004). The results demonstrate weak associations between different coping strategies. Conclusion: the coping strategy chosen by women with breast cancer is directly related to anxiety. Patients with low-level anxiety tend to use problem-solving strategies while emotion-focused coping is applied if the level is medium to high.